Quench energy studies in ITER conductors for different magnetic field perturbations with Jackpot and THEA combined models. (23rd July 2018) - Bagni, T; Duchateau, J L; Devred, A; Nijhuis, A
Abstract: The electromagnetic–thermal models for the cable-in-conduit conductors (CICCs) JackPot-ACDC and THEA (thermal, hydraulic and electric analysis of superconducting cables) are combined to predict the stability of ITER central solenoid conductors. The combination of both models allows the prediction of the effect of any type of magnetic field perturbation in time, relevant for the magnet coils during the plasma operation scenario of the reactor. At present, there is no experiment for testing the stability of the ITER Nb3 Sn conductors under such conditions. Only limited experimental data on minimum quench energy (MQE), defining the conductor stability, are available but the time and magnetic field amplitude settings are completely different from the actual ITER operating conditions. Nevertheless, such tests are useful as a basis to calibrate and benchmark the codes. The JackPot-THEA combination allows us to determine the MQE for any magnetic field change in time and to fully describe the involved electromagnetic phenomena in strand-level detail in terms of local power dissipation and (peak) electric field along all strands. Thermally, the computation is still on a global scale for identifying the quench initiation and propagation. The predictions from the combined codes are in good agreement with the experimental results and provide a solid basis for extrapolative scaling of the stability of CICCs under plasma operating conditions.